2019
DOI: 10.1190/geo2018-0039.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave-equation dispersion inversion of Love waves

Abstract: We present a theory for wave-equation inversion of Love-wave dispersion curves, in which the misfit function is the sum of the squared differences between the wavenumbers along the predicted and observed dispersion curves. Similar to inversion of Rayleigh-wave dispersion curves, the complicated Love-wave arrivals in traces are skeletonized as simpler data, namely, the picked dispersion curves in the [Formula: see text] domain. Numerical solutions to the SH-wave equation and an iterative optimization method are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…These curves are then inverted by the wave‐equation dispersion inversion method (Li et al . ) and the inverted S‐velocity tomogram is shown in Fig. .…”
Section: Numerical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…These curves are then inverted by the wave‐equation dispersion inversion method (Li et al . ) and the inverted S‐velocity tomogram is shown in Fig. .…”
Section: Numerical Testsmentioning
confidence: 99%
“…Li et al . () used the WD S‐velocity tomogram to infer a LVZ in this area. The seismic data are recorded over the Qademah fault, where the shot spacing is 10 m, the vertical‐component receiver spacing is 5 m, and there are 120 traces per shot gather to give a total of 60 shot gathers.…”
Section: Numerical Testsmentioning
confidence: 99%
“…A 90 kg weight drop is used as the seismic source, with 10 to 15 stacks at each shot location. Inverting the Love waves gives a low-S-velocity zone (LVZ) above 20 m in the middle of site 2 (Li et al, 2017b).…”
Section: Qademah Field Datamentioning
confidence: 99%
“…Xia et al (2012) demonstrated that higher signal to noise in dispersion images of Love-wave energy is the main advantage of using the multichannel analysis of Love-waves to obtain S-wave velocity profiles. Li et al (2019) found Love-wave dispersion curve produced better convergence properties than that of Rayleigh waves in their presented wave-equation-based inversion method.…”
Section: Introductionmentioning
confidence: 96%